Imagery in Dr. Kedarnath Singh’s Poetry: A Cultural and Aesthetic Study: डॉ० केदारनाथ सिंह की कविता में बिंब-विधान: एक सांस्कृतिक और सौंदर्यात्मक अध्ययन - Tiwari, Shivam (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Dr. Kedarnath Singh is one of the prominent poets of contemporary Hindi literature, whose poetic language reflects a remarkable synthesis of deep imagery, sensitivity, and cultural consciousness. A major aspect of his poetry is his use of imagery, through which he renders his thoughts, experiences, and emotions so concrete and visual that the reader doesn’t just read them, but also sees, feels, and connects with them on a personal level. The images employed in his poems—such as village, soil, water, window, leaves, mother, and words—are not merely decorative visuals, but powerful symbols of worldview, cultural roots, and memories. For example, the image of a ‘window’ is not just an architectural element but becomes a medium of open vision and dialogue for the soul. Similarly, the image of ‘mother’ transcends mere motherhood and becomes a symbol of sensitivity and identity. Kedarnath Singh’s use of imagery is not just an aesthetic expression but a structure for conveying deep meaning and communication in poetry. He reshapes traditional symbols in such a way that they deeply connect with contemporary reality. His imagery transforms language into a visual experience, where complex ideas appear simple. This imagistic structure moves the reader on emotional, intellectual, and mnemonic levels and takes them on a journey through a vivid visual world within the poem, leaving a lasting impact on their inner self. Abstract in Hindi Language: डॉ० केदारनाथ सिंह समकालीन हिंदी कविता के उन कवियों में हैं, जिनकी काव्य-भाषा में गहन बिंबात्मकता, संवेदना और सांस्कृतिक चेतना का विलक्षण समन्वय दिखाई देता है। उनकी कविता का एक प्रमुख पक्ष बिंब-विधान है, जिसके माध्यम से वे अपने विचारों, अनुभूतियों और भावनाओं को इतना मूर्त और दृश्यात्मक बना देते हैं कि पाठक उन्हें केवल पढ़ता नहीं, बल्कि देखता, महसूस करता और उनसे आत्मीयता के स्तर पर जुड़ता है। उनकी कविताओं में प्रयुक्त बिंब – जैसे गाँव, मिट्टी, पानी, खिड़की, पत्तियाँ, माँ और शब्द – केवल दृश्य सज्जा नहीं, बल्कि जीवन-दृष्टि, सांस्कृतिक जड़ों और स्मृतियों का सशक्त प्रतीक होते हैं। उदाहरण के लिए, ‘खिड़की’ का बिंब केवल वास्तु का हिस्सा न रहकर आत्मा की खुली दृष्टि और संवाद का माध्यम बन जाता है, वहीं ‘माँ’ का बिंब मातृत्व से आगे बढ़कर संवेदना और पहचान का प्रतीक बन जाता है। केदारनाथ सिंह का बिंब-विधान केवल सौंदर्यपरक अभिव्यक्ति नहीं, बल्कि कविता के गहरे अर्थबोध और संप्रेषण की संरचना है। वे पारंपरिक प्रतीकों को नए संदर्भों में इस तरह ढालते हैं कि वे समकालीन यथार्थ के साथ गहराई से जुड़ जाते हैं। उनका बिंब-विधान भाषा को एक दृश्यात्मक अनुभव में बदल देता है, जहाँ विचार जटिल होते हुए भी सरल प्रतीत होते हैं। यह बिंबीय संरचना पाठक को भाव, विचार और स्मृति – तीनों स्तरों पर आंदोलित करती है और उसे कविता के भीतर एक जीवंत दृश्य-जगत की यात्रा कराती है, जो उसके अंतर्मन में स्थायी प्रभाव छोड़ता है। Keywords: डॉ० केदारनाथ सिंह, बिंब-विधान, दृश्यात्मकता, सांस्कृतिक चेतना, ग्राम्य जीवन, संप्रेषणीयता, प्रतीकात्मकता।